Crystal Structures and Phase Behavior of Sulfadiazine and a Method for the Preparation of Aggregates with Good Performance. Issue 3 (3rd January 2018) - Wu, Songgu; Du, Shichao; Chen, Mingyang; Li, Kangli; Jia, Lina; Zhang, Dejiang; Macaringue, Estevao G. J.; Hou, Baohong; Gong, Junbo
Abstract: The solvate and the solvent‐free form of sulfadiazine (SD) were investigated. SD was found to exist in one solvent‐free form and the N ‐methylpyrrolidone (NMP) solvate form. The NMP solvate was shown to be a channel‐type compound. The intrinsic properties of the solvents were used to evaluate the effects of solubility on the phase transformation of SD and the NMP solvate. The SD phase could transform to the NMP solvate by NMP‐mediated phase transformation, which was governed by crystallization of the NMP solvate. The crystalline NMP solvate could transform to the solvent‐free solid state through solid‐solid transformation upon heating or water penetration‐mediated phase transformation. The rate of this water penetration‐mediated phase transformation of the NMP solvate to SD was unusually fast. It can be used to obtain SD aggregates of well‐defined shape and good powder properties. Abstract : Sulfadiazine (SD) exists in one solvent‐free form and the N ‐methylpyrrolidone (NMP) solvate form, with the NMP solvate being a channel‐type compound. The SD phase can transform to the NMP solvate by NMP‐mediated phase transformation. Water penetration‐mediated phase transformation of the NMP solvate to SD can be used to obtain SD aggregates of well‐defined shape and good powder properties.